KARAKTERISTIK SPEKTRAL TANAMAN PADI VARIETAS UNGGUL DALAM FASE PERTUMBUHAN PADA DATA DIGITAL LANDSAT THEMATIC MAPPER (THE SPECTRAL CHARACTERISTICS OF PADDY ON THE GROWTH PHASE ON LANDSAT THEMATIC MAPPER DIGITAL DATA) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT Knowledge on vegetation spectral characteristics is needed in remote sensing system especially the reflectance value that is used to assess the condition, type and age of vegetation. Therefore, the reflectance curve of paddy on growth phase is studied remote sensing technology. The study was carried out on spectral characteristic of paddy on growth phase from the result of laboratory test and the Landsat TM data digital analysis for each band except TM-6 band. This article describs the reflectance curve of paddy leaves chlorophyll on growth phase from the result of laboratory test used Spectrophotometer detector and the statistic analysis to the changing analysis of the average reflectance value of paddy on Landsat TM digital data to the pixel in grey scale value by used ENVI 3.1 for window software. The result of laboratory analysis shows that the 1R-64 and Mamberamo paddy leaves pigment (chlorophyll) on growth phase have strong reflectance in the blue and red spectrums, but relatively weak in green spectrum. The reflectance differentiation appears after the 1st week in planting season for blue wavelength band and the 7th week for green wavelength band. Bisides, based on the analysis of the average reflectance value of paddy on Landsat TM digital data, it is recognized that in the visible spectrum of TM-1 and TM-3 have higher reflectance than that of TM-2.